ПАРЛАМЕНТЫН ЁС ЗҮЙН СУДАЛГАА БА ХӨГЖИЛ - Д.Ундрах, (Politology, 2023)
Ардчиллын бэхжилт, парламентат ёсны төлөвшил, засаглалын үр дүнтэй, тогтвортой хөгжлийн асуудлыг хариуцлага, ёс зүйгүйгээр төсөөлөхийн аргагүй. Эрх зүйт төрийг цогцлоон байгуулах ажлын суурь үндэс хууль тогтоогчдын ёс зүйн хэм хэмжээний ёсзүйн зохилуулалт хяналтын тогтолцоог бүрдүүлэхтэй нягт уялдана. Abstract: Since its democratic transition started in early 1990s, Mongolia has acheived relatively well in establishing democratic institutions and making legal reform. Institutional part of refers the way of process with its success and failure, and this part of work has been examined and surveyes in some extent by local and foreign experts and researchers. Even though, subjective factors that appear through tradition and cultures and, value and assessment system of individuals in a society are not considered a less recognized during this era of transition. Then when we face failures of reform. instability of social economic life and "back wave threat" to democracy, we start to seek the "missed and changed" regulatory effect of ethical and moral norms. Especially, the ethics of law makers are crucially important to be regulated and enforced.